Synthesis of very low density lipoproteins in the cockerel. Effects of estrogen. - Chan, L (1976)
The effect of estrogen on the synthesis of plasma very low density lipoproteins (VLDL) in the cockerel was studied both in vivo and in vitro. Synthesis was studied by immunoprecipitation techniques with antisera prepared against VLDL and a major VLDL protein. VLDL were isolated from the plasma of white Leghorn hens and estrogen-treated white Leghorn cockerels by ultracentrifugal flotation at d 1.006 g/ml. After delipidation, the lipid-free proteins (apoproteins) were fractionated on Sephadex G-150 and DEAE-cellulose. Both the hen and the estrogen-treated cockerel VLDL were shown to contain an identical apoprotein with a mol wt of approximately 12,000; the apoprotein is designated fraction B. Reduction and S-carboxy-methylation of fraction B resulted in a reduction of the molecular weight by approximately one-half, indicating a dimer-monomer relationship. Antiserum prepared to the hen VLDL dimer protein gave precipitin lines of complete identity to both the hen and cockerel dimer, monomer, VLDL, apoVLDL, low density lipoproteins, and plasma; no precipitin line was formed with either hen or cockerel high density lipoproteins. After a single subcutaneous injection of diethylstilbestrol into the cockerel, plasma VLDL protein, cholesterol, and triglyceride increased, reaching a maximum 24--48 h after hormone administration. Liver slices from similarly treated animals were incubated in vitro in culture medium in the presence of [3H]lysine for 2 h. Immunoprecipitable radioactivity in VLDL increased within 2 h of diethylstilbestrol treatment and reached a maximum at 24 h; VLDL radioactivity returned to base-line levels by 72 h. At the peak of induction, newly synthesized VLDL represented 11% of the total soluble protein synthesized. When actinomycin-D (5 mg/kg) was administered simultaneously with estrogen, the induction of VLDL synthesis was totally inhibited. To determine whether the effect of estrogen on VLDL synthesis was mediated at the level of transcription, partially-purified cockerel liver mRNA was prepared from estrogen-treated animals and the mRNA activity for fraction B was quantitated in a wheat germ translation system. Fraction B mRNA was found to increase from a low base-line value to a maximum 16-24 h after estrogen treatment, returning towards baseline values at 30 h. At the peak of induction, fraction B constituted 12% of the total protein synthesized. The kinetics of induction of fraction B mRNA activity in the cell-free translation system is very similar to that observed in liver slice experiments. This finding suggests that estrogen stimulates VLDL synthesis, at least partially, by enhancing the accumulation of the mRNA for one of their major apoproteins.